¿La Educación Sexual puede ser gestionada por la Pedagogía? Una revisión por los planes y programas del MINEDUC y breves consideraciones para educadores y educadoras del país (Boletín de Políticas y Gestión Educativa, 2022)
From formal education, each participant is clear about their tasks: the teacher teaches, the student listens and the evaluation is carried out. The creation of ties to deal with issues such as sexuality becomes complicated, and all this, is regulated the institutional levels that currently govern, but there is Informal Education, that in which the language is rhetorical, the themes, interesting, the pleasant and collaborative environment and attend, a pleasure. So, where can a cross between the two be achieved that generates integral learning spaces? This paper invites you to learn about the Sex Education experienced by children and young people in their different contexts. In addition, it makes a tour of the experiences of these and practicing teachers and how the plans and programs in an incipient way, try to reach an Education that visualizes sexuality as self-care, affection and companionship.
Keywords: Pedagogy- Popular Education -Sexuality